Termination And Consequences Of Ear Farms In The Districts Of Fergana, Tashkent, Samarkand. - Qambarova Shoiraxon Asqarovna (Genius Journals, 2023)
This article outlines land and water reform in the Central Asian republics, which are part of the Soviet Union, in the provinces of Fargo, Tashkent, and Samarkand
Keywords: Ear; Central Asian Republics; Stalin; Farmers